Suppression of p53 activity and p21WAF1/CIP1 expression by vascular cell integrin alphaVbeta3 during angiogenesis. - Strömblad, S (1996)
Induction of p53 activity in cells undergoing DNA synthesis represents a molecular conflict that can lead to apoptosis. During angiogenesis, proliferative endothelial cells become apoptotic in response to antagonists of integrin alphavbeta3 and this leads to the regression of angiogenic blood vessels, thereby blocking the growth of various human tumors. Evidence is presented that administration of alphavbeta3 antagonists during angiogenesis in vivo selectively caused activation of endothelial cell p53 and increased expression of the p53-inducible cell cycle inhibitor p21WAF1/CIP1. In vitro studies revealed that the ligation state of human endothelial cell alphavbeta3 directly influenced p53 activity and the bax cell death pathway. Specifically, agonists of endothelial cell alphavbeta3, but not other integrins, suppressed p53 activity, blocked p21WAF1/CIP1 expression, and increased the bcl-2/bax ratio, thereby promoting cell survival. Thus, ligation of vascular cell integrin alphavbeta3 promotes a critical and specific adhesion-dependent cell survival signal during angiogenesis leading to inhibition of p53 activity, decreased expression of p21WAF1/CIP1, and suppression of the bax cell death pathway.